Antioxidant Capacity Assays by Sequential Injection Analysis using a Peristaltic Pump and Low-Cost Amperometric Detection with Pencil Lead Electrodes - Meanha, Pachara; Kongkedsuk, Jakkrapun; Hongwitayakorn, Apisake; Chaisuksant, Rasamee (Agriculture and Natural Resources, 2015)
Miniaturization of electrode and flow cell assemblies was accomplished using low-cost pencil graphite leads and micropipette tips for sequential injection analysis (SIA) with amperometric detection (AD). The Masterflex peristaltic pump of the SIA-AD system was semi-automatically controlled by the in-house electronic circuit controller and pump drive computer software written in the Processing language. The developed SIA-AD was applied to rapid screening tests of antioxidant capacity by 2,2′azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay and reducing capacity measurement. By ABTS assay, the cathodic current signal of the ABTS cation radicals left after the reaction with the antioxidants in the sample was monitored at the applied potential -0.10 V vs. Ag/AgCl whereas by the reducing power measurement, anodic current from oxidation of antioxidants in the sample at +0.50 V vs. Ag/AgCl was detected. The peak current from each sample assay was calibrated with a gallic acid (GA) antioxidant standard conducted using the same procedure and expressed as the total antioxidant capacity of the sample in equivalent units (GAE). The total antioxidant capacities of some herb infusions were determined by ABTS assay and reducing power measurement using the proposed SIA-AD with sample throughputs of 22 and 36 samples/hr, respectively. Classical spectrophotometric ABTS assay was also carried out for comparison. The total antioxidant capacities in GAE found in the herb samples by all assays were in consensus for the series with black tea >> cinnamon > ginger > safflower ≈ chrysanthemum.